2023
DOI: 10.1021/acs.jced.3c00129
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Solubility and Molecular Simulation of Dissolution Behavior of Isonicotinamide in 15 Pure Solvents

Wenju Liu,
Xiaolong Yang,
Haoqing Zhang
et al.

Abstract: The solubility of isonicotinamide­(INA) in 15 pure solvents (including N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol, n-propanol, iso-propanol, n-butanol, n-pentanol, tetrahydrofuran, ethyl acetate, methyl acetate, acetonitrile, n-propyl acetate, iso-propyl acetate, acetone) has been measured (P = 0.1 MPa, T = (278.15–323.15 K)) by the gravimetric method. At 323.15 K, the order of solubility of INA­(P21/c) in 15 mono-solvents was N,N-dimethylacetamide ≥ N,N-dimethylformamide ≥ methanol ≥ etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The d norm map was used to get the 2D fingerprints. Hirshfeld-related research on INA (P21C) is found from a related article by previous authors Liu et al…”
Section: Methodsmentioning
confidence: 99%
“…The d norm map was used to get the 2D fingerprints. Hirshfeld-related research on INA (P21C) is found from a related article by previous authors Liu et al…”
Section: Methodsmentioning
confidence: 99%